Percepção e utilização da caderneta da criança por profissionais e cuidadores - Soares, Anniely Rodrigues (2021)
Introduction: Health monitoring in early childhood is paramount for a sound and orderly surveillance of the development of the child. For this purpose, the child’s booklet represents a supportive tool for integral care. Objectives: Understand both the perception of Family Health strategy professionals, as well as of caregivers of children under three years of age on the child’s booklet and knowledge of its use. Methodological procedure: Qualitative, descriptiveexploratory study under the theoretical lens of Symbolic Interactionism carried out with 25 health professionals and 11 caregivers. The production of data took place from September to October of 2020 through semistructured interviews at Family Health Units. The data set was analyzed under the inductive thematic analysis technique.The research was approved by the ethic committee under the Certificate of Ethical Appraisal Submission: 97362718.1.0000.5188. Results: The Child’s booklet is understood as both a multiprofissional and intersectorial document which promotes the child's health and ensures continuity of care. The use of the booklet occurs according to the meaning that is attributed to it, and it is implemented, most often, by nurses during childcare consultations and perceived as guiding the professional's conduct. When used by the caregivers, it serves to remove doubts that arise during child care. However, terms such as “vaccination card” and “vaccination booklet” are still present in the data extracts, as if the booklet had this purpose only. Obstacles to the use of this tool were identified, but strategies to promote its use were also pointed out. Final considerations: The perception of Family Health professionals and caregivers about the booklet was consistent with its propositions. In contradiction, it was not used for both surveillance and promotion of child health. Thus, awareness-raising strategies aimed at those involved in child care are paramount in order to give new meaning and values to the booklet and promote the continuity and completeness of care in childhood.